استشكلات فاطمة المرنيسي لأحاديث المرأة من خلال كتابها: " الحريم السياسي- النبي والنساء - دراسة نقدية - صوالح عماره, أسماء; حشيفة, سليمة (University of Eloued جامعة الجزائر, 2020)
" الحمد لله والصلاة والسلام على خير الأنام نبينا محمد وعلى آله وصحبه ومن والاه. تتحدث دراستنا هذه عن أحد أقطاب الفكر الحداثي والاتجاه اليساري، أو ما يسمى اليوم بالتنويريين؛ وكيف كان تعاملهم مع الأحاديث النبوية وشبهاتهم المختلقة حولها، من بينهم عالمة الاجتماع المغربية ""فاطمة المرنيسي ( 1940- 2015 م)""، وجاءت الدراسة بعنوان ""استشكالات فاطمة المرنيسي لأحاديث المرأة من خلال كتابها الحريم السياسي – النبي والنّساء""، وتضمنت الدراسة مناقشة ما استشكلته في كتابها المذكور، والرد عليها وفق منهج علمي. ""Praise be to Allah, and may blessings and Allah be upon the most honored of human beings, our Prophet Muhammad, his family, companions. In this study, we talk about one of the poles of modernist thought and the leftist, or what is called today the ""Enlightenment"". Besides, how was their interaction with the hadiths and their false suspicions about them. Among them there is the Moroccan sociologist called Fatima Mernissi (1940-2015). Under her publication that entitled ""Issues of Fatima Mernissi for Women’s Hadiths"" within her book, which entitled "" The Political Harem - The Prophet and the Women –"". With these considerations, we attempts to highlight this issue. Moreover, criticizing these claims based on a scientific method.
مذكرة ماستر تخصص الحديث وعلومه
Keywords: "فاطمة المرنيسي - الحريم السياسي - مشكل الحديث"; Fatima ALmarnisi-ALharim de Politique-Proplem de Hadith